Development and characterisation of integrated wet-spun alginate-Moringa oleifera composite fibers for potential water purification - Orisawayi, Abimbola Oluwatayo; Koziol, Krzysztof K.; Rahatekar, Sameer S. (Elsevier, 2025)
Ensuring access to safe drinking water requires effective materials and technologies to treat contaminated water. In this study, we developed sodium alginate fibre (SAlgF) and their composite fibres functionalised with pulverised Moringa oleifera (MoP) at concentrations of 0.5 %, 1 %, 4 %, and 8 % using the wet-spinning technique. Both SAlgF and MoP are biodegradable, offering eco-friendly alternatives to synthetic polymers in line with green manufacturing. The results showed significant improvements in the mechanical properties, with the 1 % MoP composite fibre exhibiting 6 times the strength of pure SAlgF in terms of ultimate tensile strength (UTS) and Young's modulus (YM). X-ray Diffraction (XRD) analysis revealed enhanced fibres interactions, while Fourier Transform Infrared Spectroscopy (FTIR) and Thermogravimetric Analysis (TGA) confirmed the successful incorporation of MoP into the alginate matrix and improved thermal stability. Furthermore, the result obtained from the Scanning Electron Microscopy-Energy Dispersive X-ray Spectroscopy (SEM-EDX) indicated morphological changes and the uptake of heavy metal ions when immersed into solutions containing Cu²⁺, Ni²⁺, and Cd²⁺. These findings demonstrate the potential of MoP-modified composite fibres for sustainable and cost-effective water treatment applications, particularly in developing countries.
Keywords: 40 Engineering; 4016 Materials Engineering; 3403 Macromolecular and materials chemistry; 3406 Physical chemistry; 4004 Chemical engineering; Sodium alginate; Moringa oleifera; Biodegradable polymers; Wet-spinning; Water treatment; Composite fibre